In vivo and In vitro Drug Interactions Study of Glimepride with Atorvastatin and Rosuvastatin - Galani, VJ (Medknow Publications, 2010)
Aim of this investigation was to study the in vivo and in vitro drug interaction of glimepride with atorvastatin and rosuvastatin. In vitro drug interaction of glimepride with atorvastatin and rosuvastatin was studied using human pooled liver microsomes and evaluated using high performance liquid chromatography. In vivo pharmacokinetic drug interaction of glimepride (6 mg/kg) in coadministration with atorvastatin (60 mg/kg) and rosuvastatin (60 mg/kg) were studied in rats and analyzed using liquid chromatography tandem mass spectrometry (LC–MS/MS). In in vitro study, atorvastatin decreased its own metabolism as well as the metabolism of glimepiride. Rosuvastatin coadministration with glimepride reduced the metabolism of glimepride and increased the metabolism of its own. In in vivo study, concentration in plasma, C(max), AUC((0–t)) and AUC((0–∞)) (area under the concentration-time curve, AUC) of glimepride was increased significantly in coadministration with atorvastatin whereas there was no significant change was observed in the case of coadministration with rosuvastatin. Half life (T(1/2)) and volume of distribution (V(d)) of glimepride decreased significantly with both atorvastatin and rosuvastatin. Elimination rate constant, K(el) of glimepride increased significantly with both atorvastatin and rosuvastatin. Clearance (Cl) of glimepride decreased significantly but the decrease was more with atorvastatin than with rosuvastatin. It is concluded that glimepride metabolism is little affected by rosuvastatin in vitro, which agreed with the negligible interaction in in vivo study. Thus, from safety point of view rosuvastatin is better to prescribe as a coadministration therapy with glimepiride. On the other hand, atorvastatin could cause an increase in the bioavailability of glimepride per oral and also significantly decrease the metabolism of glimerpride in in vitro study. This may pose a positive implication in clinical practice.